Visual Arts in Nursing Education: An Inventive Interprofessional Initiative to Cultivate Metacognitive Awareness in Beginning Nursing Students. (June 2021) - Lovell, Carley; Elswick, R. K.; McKay, Sara Wilson; Robins, Jo; Salyer, Jeanne
Purpose: To test an interdisciplinary art-based educational program for beginning baccalaureate traditional and accelerated nursing students. Design: Longitudinal study (Pretest–Posttest) of nursing students' metacognitive awareness. Method: As part of a first-semester foundations nursing course, all students participated in the Art of Nursing program consisting of three 90-minute sessions led by graduate Art Education students in a local fine arts museum. Before and after the program, subcomponents of critical thinking were assessed using the Metacognitive Awareness Inventory (MAI). Findings: A total of 218 students (56 traditional, 162 accelerated) participated. Statistically significant improvement was observed on seven components of the MAI. Although significant increases were observed for Declarative ( p < .0001), Planning ( p < .0001), and Comprehension Monitoring ( p < .0001), the differences pre to post were of different magnitudes between the student groups, characterizing a large change in the traditional versus accelerated group. Conclusions: Our results suggest that (1) nursing students' metacognitive awareness benefits from the museum-based experience despite demographic and educational differences and (2) overall the accelerated student group has exhibited higher metacognitive awareness at baseline as compared with the traditional student group; however, both groups demonstrate significant growth in this area after experiencing an art-based program.